Climate change and its impacts in South Africa - Jaarsveld, A. S. van; Chown, Steven L. (Trends in Ecology and Evolution, 2001)
The South African Country Study on Climate Change was hosted by the South African National Research Foundation in Pretoria, Gauteng, South Africa, on 22 August 2000.
Keywords: openalex:import

Vulnerability of South African animal taxa to climate change - Erasmus, Barend; Jaarsveld, A. S. van; Chown, Steven L.; Kshatriya, Mrigesh; Wessels, Konrad J (Global Change Biology, 2002)
Abstract The responsiveness of South African fauna to climate change events is poorly documented and not routinely incorporated into regional conservation planning. We model the likely range alterations of a representative suite of 179 animal species to climate change brought about by the doubling of CO 2 concentrations. This scenario is expected to cause a mean temperature increase of 2 °C. We applied a multivariate climate envelope approach and evaluated model performance using the most comprehensive bird data set. The results were encouraging, although model performance was inconsistent in the eastern coastal area of the country. The levels of climate change induced impacts on species ranges varied from little impact to local extinction. Some 17% of species expanded their ranges, 78% displayed range contraction (4–98%), 3% showed no response and 2% became locally extinct. The majority of range shifts (41%) were in an easterly direction, reflecting the east–west aridity gradient across the country. Species losses were highest in the west. Substantially smaller westward shifts were present in some eastern species. This may reflect a response to the strong altitudinal gradient in this region, or may be a model artifact. Species range change (composite measure reflecting range contraction and displacement) identified selected species that could act as climate change indicator taxa. Red‐data and vulnerable species showed similar responses but were more likely to display range change (58% vs. 43% for all species). Predictions suggest that the flagship, Kruger National Park conservation area may loose up to 66% of the species included in this analysis. This highlights the extent of the predicted range shifts, and indicates why conflicts between conservation and other land uses are likely to escalate under conditions of climate change.
Keywords: openalex:import

Vulnerability of South African animal taxa to climate change - Erasmus, Barend; Jaarsveld, A. S. van; Chown, Steven L.; Kshatriya, Mrigesh; Wessels, Konrad J (Global Change Biology, 2002)
Abstract The responsiveness of South African fauna to climate change events is poorly documented and not routinely incorporated into regional conservation planning. We model the likely range alterations of a representative suite of 179 animal species to climate change brought about by the doubling of CO 2 concentrations. This scenario is expected to cause a mean temperature increase of 2 °C. We applied a multivariate climate envelope approach and evaluated model performance using the most comprehensive bird data set. The results were encouraging, although model performance was inconsistent in the eastern coastal area of the country. The levels of climate change induced impacts on species ranges varied from little impact to local extinction. Some 17% of species expanded their ranges, 78% displayed range contraction (4–98%), 3% showed no response and 2% became locally extinct. The majority of range shifts (41%) were in an easterly direction, reflecting the east–west aridity gradient across the country. Species losses were highest in the west. Substantially smaller westward shifts were present in some eastern species. This may reflect a response to the strong altitudinal gradient in this region, or may be a model artifact. Species range change (composite measure reflecting range contraction and displacement) identified selected species that could act as climate change indicator taxa. Red‐data and vulnerable species showed similar responses but were more likely to display range change (58% vs. 43% for all species). Predictions suggest that the flagship, Kruger National Park conservation area may loose up to 66% of the species included in this analysis. This highlights the extent of the predicted range shifts, and indicates why conflicts between conservation and other land uses are likely to escalate under conditions of climate change.
Keywords: openalex:import

Vulnerability of South African animal taxa to climate change - Erasmus, Barend; Jaarsveld, A. S. van; Chown, Steven L.; Kshatriya, Mrigesh; Wessels, Konrad J (Global Change Biology, 2002)
Abstract The responsiveness of South African fauna to climate change events is poorly documented and not routinely incorporated into regional conservation planning. We model the likely range alterations of a representative suite of 179 animal species to climate change brought about by the doubling of CO 2 concentrations. This scenario is expected to cause a mean temperature increase of 2 °C. We applied a multivariate climate envelope approach and evaluated model performance using the most comprehensive bird data set. The results were encouraging, although model performance was inconsistent in the eastern coastal area of the country. The levels of climate change induced impacts on species ranges varied from little impact to local extinction. Some 17% of species expanded their ranges, 78% displayed range contraction (4–98%), 3% showed no response and 2% became locally extinct. The majority of range shifts (41%) were in an easterly direction, reflecting the east–west aridity gradient across the country. Species losses were highest in the west. Substantially smaller westward shifts were present in some eastern species. This may reflect a response to the strong altitudinal gradient in this region, or may be a model artifact. Species range change (composite measure reflecting range contraction and displacement) identified selected species that could act as climate change indicator taxa. Red‐data and vulnerable species showed similar responses but were more likely to display range change (58% vs. 43% for all species). Predictions suggest that the flagship, Kruger National Park conservation area may loose up to 66% of the species included in this analysis. This highlights the extent of the predicted range shifts, and indicates why conflicts between conservation and other land uses are likely to escalate under conditions of climate change.
Keywords: openalex:import

Vulnerability of South African animal taxa to climate change - Erasmus, Barend; Jaarsveld, A. S. van; Chown, Steven L.; Kshatriya, Mrigesh; Wessels, Konrad J (Global Change Biology, 2002)
Abstract The responsiveness of South African fauna to climate change events is poorly documented and not routinely incorporated into regional conservation planning. We model the likely range alterations of a representative suite of 179 animal species to climate change brought about by the doubling of CO 2 concentrations. This scenario is expected to cause a mean temperature increase of 2 °C. We applied a multivariate climate envelope approach and evaluated model performance using the most comprehensive bird data set. The results were encouraging, although model performance was inconsistent in the eastern coastal area of the country. The levels of climate change induced impacts on species ranges varied from little impact to local extinction. Some 17% of species expanded their ranges, 78% displayed range contraction (4–98%), 3% showed no response and 2% became locally extinct. The majority of range shifts (41%) were in an easterly direction, reflecting the east–west aridity gradient across the country. Species losses were highest in the west. Substantially smaller westward shifts were present in some eastern species. This may reflect a response to the strong altitudinal gradient in this region, or may be a model artifact. Species range change (composite measure reflecting range contraction and displacement) identified selected species that could act as climate change indicator taxa. Red‐data and vulnerable species showed similar responses but were more likely to display range change (58% vs. 43% for all species). Predictions suggest that the flagship, Kruger National Park conservation area may loose up to 66% of the species included in this analysis. This highlights the extent of the predicted range shifts, and indicates why conflicts between conservation and other land uses are likely to escalate under conditions of climate change.
Keywords: openalex:import; openalex:yes

Vulnerability of South African animal taxa to climate change - Erasmus, Barend; Jaarsveld, A. S. van; Chown, Steven L.; Kshatriya, Mrigesh; Wessels, Konrad J (Global Change Biology, 2002)
Abstract The responsiveness of South African fauna to climate change events is poorly documented and not routinely incorporated into regional conservation planning. We model the likely range alterations of a representative suite of 179 animal species to climate change brought about by the doubling of CO 2 concentrations. This scenario is expected to cause a mean temperature increase of 2 °C. We applied a multivariate climate envelope approach and evaluated model performance using the most comprehensive bird data set. The results were encouraging, although model performance was inconsistent in the eastern coastal area of the country. The levels of climate change induced impacts on species ranges varied from little impact to local extinction. Some 17% of species expanded their ranges, 78% displayed range contraction (4–98%), 3% showed no response and 2% became locally extinct. The majority of range shifts (41%) were in an easterly direction, reflecting the east–west aridity gradient across the country. Species losses were highest in the west. Substantially smaller westward shifts were present in some eastern species. This may reflect a response to the strong altitudinal gradient in this region, or may be a model artifact. Species range change (composite measure reflecting range contraction and displacement) identified selected species that could act as climate change indicator taxa. Red‐data and vulnerable species showed similar responses but were more likely to display range change (58% vs. 43% for all species). Predictions suggest that the flagship, Kruger National Park conservation area may loose up to 66% of the species included in this analysis. This highlights the extent of the predicted range shifts, and indicates why conflicts between conservation and other land uses are likely to escalate under conditions of climate change.
Keywords: openalex:import; openalex:yes

Vulnerability of South African animal taxa to climate change - Erasmus, Barend; Jaarsveld, A. S. van; Chown, Steven L.; Kshatriya, Mrigesh; Wessels, Konrad J (Global Change Biology, 2002)
Abstract The responsiveness of South African fauna to climate change events is poorly documented and not routinely incorporated into regional conservation planning. We model the likely range alterations of a representative suite of 179 animal species to climate change brought about by the doubling of CO 2 concentrations. This scenario is expected to cause a mean temperature increase of 2 °C. We applied a multivariate climate envelope approach and evaluated model performance using the most comprehensive bird data set. The results were encouraging, although model performance was inconsistent in the eastern coastal area of the country. The levels of climate change induced impacts on species ranges varied from little impact to local extinction. Some 17% of species expanded their ranges, 78% displayed range contraction (4–98%), 3% showed no response and 2% became locally extinct. The majority of range shifts (41%) were in an easterly direction, reflecting the east–west aridity gradient across the country. Species losses were highest in the west. Substantially smaller westward shifts were present in some eastern species. This may reflect a response to the strong altitudinal gradient in this region, or may be a model artifact. Species range change (composite measure reflecting range contraction and displacement) identified selected species that could act as climate change indicator taxa. Red‐data and vulnerable species showed similar responses but were more likely to display range change (58% vs. 43% for all species). Predictions suggest that the flagship, Kruger National Park conservation area may loose up to 66% of the species included in this analysis. This highlights the extent of the predicted range shifts, and indicates why conflicts between conservation and other land uses are likely to escalate under conditions of climate change.
Keywords: openalex:import

Conservation during times of change: correlations between birds, climate and people in South Africa - Rensburg, Berndt J. van; Erasmus, Barend; Jaarsveld, A. S. van; Gaston, Kevin J.; Chown, Steven L. (South African Journal of Science, 2004)
Few studies have investigated the ability of national conservation networks to adapt to changes in underlying environmental drivers (such as precipitation) and their consequences for factors such as human density and species richness patterns. In this article, the South African avifauna is used as the basis for such analysis to ascertain the likely extent of current, and future, anthropogenic impacts on priority conservation areas. We show that human population pressure is high in or around most of these priority areas and is likely to increase, given the magnitude of post-climate change estimated from predicted changes in precipitation and relationships between species richness, human densities, and rainfall. Although additional conservation areas, such as the Important Bird Area (IBA) network, are likely to introduce valuable flexibility to conservation management, only limited options are available for such expansions, and the conservation value of these areas is likely to be compromised by changing climate. Ultimately, a more integrated conservation approach is needed for effective conservation policies. Such an approach should confer adequate protection on current reserves and emphasize sustainable utilization of non-reserve areas.
Keywords: openalex:import